WHEN ‘HOMELAND’ IS NO LONGER ‘HOME’, THE IDENTITY CRISIS, THE LOSS OF MOBILITY, AND THEIR SOCIAL MEDIA CAMPAIGN ——A STUDY OF SOCIAL MEDIA TESTIMONIOS BY CHINESE TRANSNATIONAL WORKERS UNDER COVID-19 GLOBAL PANDEMIC - GUO, Jing (AoIR Selected Papers of Internet Research, 2021)
In this article, I apply narrative analysis to draw a picture on the life of Chinese transnational workers under Covid-19 global pandemic in 2020. I try to explore the identity, space, and emotion of Chinese transnational workers under the pandemic crisis through their testimonios on WeChat public space, which is their first-person written narratives on their bitter, and even traumatic experiences of being a transnational worker in countries under severe pandemic conditions but unable to find their way home. With Chinese government’s policy setting broad limitations on international flights, requirements of Corona virus nucleic acid testing before boarding, unaffordable flight tickets and the forced, self-financed 14-day quarantine after landing, China, as the homeland of Chinese transnational workers, closed its door and turned them away. However, their sufferings and stories are less covered by the media and known by the public. By posting testimonios in virtual space on WeChat, Chinese transnational workers from various destination countries tried to voice themselves and appeal for supports.